Elucidation of the Various Mechanisms of Antioxidant Activity of Organosulfur Compounds - Chauvin, Jean-Philippe (Université d'Ottawa / University of Ottawa, 2019)
Polysulfides, produced from olefin sulfurization, are common additives to various petroleum-derived products such as engine oils, hydraulic fluids, rubbers and polymeric materials in an effort to protect these materials from oxidative degradation. The mechanisms by which organosulfur compounds act as antioxidants are often described as ‘secondary antioxidants’ since it is believed that they slow the rate of radical initiation by decomposing hydroperoxides. Organosulfurs also figure in various natural products from the genus Allium, of which garlic is a prominent species. Our group previously shown that thiosulfinates (RS(O)SR), key components of garlic, are potent radical-trapping antioxidants (RTAs) through the intermediacy of sulfenic acids (RSOH). In an effort to shed light on the antioxidant mechanisms of other organosulfur constituents of garlic and sulfurized olefins, in Chapter 2, we reported on the antioxidant activity of trisulfide-1-oxides (RS(O)SSR) at 37 °C. In that study, we found these moieties to be effective RTAs, equal in potency to hindered phenols, the industry standard. Trisulfide-1-oxides were shown to react with peroxyl radicals via a concerted bimolecular homolytic substitution reaction, forming a perthiyl radical as product. In Chapter 3, inspired by the findings at 37 °C, we investigated the RTA activity of polysulfides at elevated temperatures, from 100 °C to 160 °C, and found that tetrasulfides were surprisingly potent RTAs at and above 100 °C. Paralleling the reactivity of trisulfide-1-oxides, tetrasulfides were found to react with peroxyl radicals via a concerted bimolecular homolytic substitution reaction, also forming a perthiyl radical as an initial product. Perthiyl radicals are formed in multiple reactions described in the abovementioned studies and although they were shown to rapidly recombine, their apparent stability, as well as preliminary computational investigations into the S-H bond strength in hydropersulfides (RSSH), prompted us to investigate hydrogen-atom transfers from hydropersulfides. As reported in Chapter 4, we found that hydropersulfides (RSSH) are very potent hydrogen-atom donors, making them highly effective RTAs in organic and aqueous media, even besting thiols in many H-atom transfer reactions with alkyl, alkoxyl and peroxyl radicals. The one-electron oxidation exhibited by hydropersulfides parallels the one we previously reported for sulfenic acids (RSOH). Previous successful studies on the one-electron oxidation of sulfenic acids prompted us to make use of the persistence imparted by a triptycene backbone to study two-electron processes, namely - thiol oxidation by hydrogen peroxide (H2O2). Indeed, the reaction of thiols with H2O2 is central to many processes essential to life, from protein folding to redox signaling. However, kinetic and mechanistic characterization of their subsequent reactions had not been reported due to the instability of the sulfenic acid intermediate under study. Gratifyingly, as reported in Chapter 5, using our triptycene model with an appended fluorine atom, we were able to investigate the complete series of consecutive reactions with hydrogen peroxide, from thiol to sulfenic acid to sulfinic acid to sulfonic acid, which has hitherto not been possible, and found that the reaction is specific base-catalyzed. Sulfinic acids (RSO2H), the primary product of sulfenic acid oxidation, have been used increasingly in recent years in many synthetic applications such as sulfonylation reactions. As described in Chapter 6, using a similar approach to previous studies, we synthesized a triptycene sulfinic acid and demonstrated that the triptycene backbone is also effective a rendering the sulfinic acid and sulfonyl radical (RSO2•) persistent enough to study H-atom transfer reactions. We showed that sulfinic acids are good H-atom donors to alkyl and alkoxyl radicals but they are not effective RTAs due to the propensity of sulfinic acids to autoxidize through the reaction of sulfonyl radicals with oxygen.
Keywords: Antioxidants; Organosulfurs; Kinetics